Layering of an annular z-pinch sheath in the presence of an axial magnetic field - Chaikovsky, Stanislav A.; Labetsky, Aleksei Yu (BEAMS 2002 : 14th International Conference on High-Power Particle Beams, Albuquerque, New Mexico, 23-28 June 2002, 2002)
Optimization of the neon K-shell radiation yield and power was performed in double-shell implosion experiments with and without an axial magnetic field. The experiments were carried out on the IMRI-5 generator, which provides a short-circuit peak current of 470 kA with a risetime of 430 ns. This paper presents experimental results which concern the z-pinch implosion time shortening in the presence of an axial magnetic field, as observed in experiments.